Ultraflexible glassy semiconductor fibers for thermal sensing and positioning - Zhang, Ting (2021)
Flexible, large-area, and low-cost thermal sensing networks with high spatial and temporal resolution are of profound importance in addressing the increasing needs for industrial processing, medical diagnosis, and military defense. Here, a thermoelectric (TE) fiber is fabricated by thermally codrawing a macroscopic preform containing a semiconducting glass core and a polymer cladding to deliver thermal sensor functionalities at fiber-optic length scales, flexibility, and uniformity. The resulting TE fiber sensor operates in a wide temperature range with high thermal detection sensitivity and accuracy, while offering ultraflexibility with the bending curvature radius below 2.5 mm. Additionally, a single TE fiber can either sense the spot temperature variation or locate the heat/cold spot on the fiber. As a proof of concept, a two-dimensional 3 × 3 fiber array is woven into a textile to simultaneously detect the temperature distribution and the position of heat/cold source with the spatial resolution of millimeter. Achieving this may lead to the realization of large-area, flexible, and wearable temperature sensing fabrics for wearable electronics and advanced artificial intelligence applications.